A reverse osmosis composite membrane and a method for preparing the same
Patent Information
- Application Number
- CN202611434449.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-20
AI Technical Summary
(1)高温稳定性不足:在70℃以上高温条件下,聚酰胺链段热运动加剧,自由体积增大,导致截盐率显著下降;同时热应力易引发膜层微裂纹
[0018]本发明将COF刚性骨架、金属配位交联、刚性四酰氯微孔三者融合,构建兼具耐高温和耐溶剂双重性能的反渗透复合膜,实现协同增强而非简单叠加,“三重交联-双通道”的协同设计,实现了1+1>2的效果,使本发明的膜片在耐溶剂和耐高温的前提下,同时保持良好的性能。三重交联-双通道即:
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of water treatment membrane technology, and in particular to a reverse osmosis composite membrane and its preparation method. Background Technology
[0002] Reverse osmosis (RO) membrane technology is the mainstream technology in fields such as seawater desalination and wastewater reuse. Traditional polyamide reverse osmosis membranes have the following limitations: (1) Insufficient high temperature stability: Under high temperature conditions above 70℃, the thermal motion of polyamide chain segments intensifies, the free volume increases, and the salt rejection rate decreases significantly; at the same time, thermal stress easily causes microcracks in the film layer.
[0003] (2) Poor solvent resistance: In wastewater containing organic solvents (such as DMF, acetone, etc.), the polyamide layer is prone to swelling, leading to performance degradation.
[0004] (3) Most studies only focus on improving performance in a single dimension (only high temperature resistance or only solvent resistance), lacking a systematic design that takes both into account. The application of covalent organic framework (COF) materials in reverse osmosis membranes is mostly concentrated on additives, and their potential for functional modification (such as metal coordination) has not been fully utilized.
[0005] In recent years, covalent organic framework (COF) nanoparticles have been used for membrane modification due to their well-ordered sub-nanopore structure. However, single-COF modification still faces the following challenges: 1. COF has limited interfacial compatibility with polyamide matrix and is prone to aggregation; 2. At high temperatures, the thermal expansion coefficients of COF and the matrix do not match, which easily leads to interface defects; 3. Limited improvement in solvent resistance.
[0006] Furthermore, tetrafunctional acyl chloride monomers (such as 2,2',4,4'-biphenyltetracarboxylic chloride) can increase crosslinking density in interfacial polymerization, but their solubility in nonpolar solvents is limited, and their synergistic effect with COF has not been fully studied. Therefore, developing a reverse osmosis composite membrane that simultaneously possesses high-temperature stability, solvent resistance, and a high flux-high salt rejection ratio is of great significance. Summary of the Invention
[0007] In view of this, the technical problem to be solved by the present invention is to provide a reverse osmosis composite membrane and a method for preparing the same. The reverse osmosis composite membrane provided by the present invention has superior high-temperature stability and solvent resistance.
[0008] The present invention provides a reverse osmosis composite membrane, comprising a non-woven fabric layer, a support layer, a polyamide separation layer and a protective layer sequentially laminated together; The polyamide separation layer is formed by interfacial polymerization of an aqueous solution and an oil solution on a support layer; the aqueous solution is obtained by adjusting the pH value of an aqueous base liquid comprising polyfunctional amines and bimetallic coordinated COF nanoparticles; the oil solution comprises pyromellitic trimethylol chloride and rigid tetramethylol chloride monomers. The protective layer is prepared on the polyamide separation layer by a post-treatment solution.
[0009] Preferably, the support layer is formed by curing a casting solution on the surface of a nonwoven fabric layer; The casting solution comprises polyimide, N-methylpyrrolidone, and hexamethylenediamine in a mass ratio of 10-20:80-90:0.75-3.75.
[0010] Preferably, the preparation method of the bimetallic coordinated COF nanoparticles includes the following steps: A. 3,3′-diamine-telegol base and 1,3,5-tricarboxymethyl phloroglucinol were ultrasonically dispersed in a mixed solvent, mixed with an aqueous acetic acid solution, degassed, and reacted at 110~130℃ to obtain COFTpDATB nanoparticles. B. An ethanol solution containing copper nitrate trihydrate and zinc nitrate hexahydrate was added dropwise to an ethanol dispersion containing COFTpDATB nanoparticles, and the reaction was carried out at 40~60℃ to obtain bimetallic coordinated COF nanoparticles.
[0011] Preferably, the mixed solvent comprises 1,4-dioxane, mesitylene, and n-butanol in a volume ratio of 4~6:0.5~1.5:0.5~1.5; The molar ratio of the 3,3′-diamine-telegol base to the 1,3,5-tricarboxymethylphloroglucinol is 0.5~1.5:0.5~1.5; The COFTpDATB nanoparticles have a particle size of 80~150 nm; The mass ratio of copper nitrate trihydrate, zinc nitrate hexahydrate, and COFTpDATB nanoparticles is 0.8~1.5:1~1.875:4.4~8.25.
[0012] Preferably, the aqueous base liquid comprises a polyfunctional amine, bimetallic coordinated COF nanoparticles, a surfactant, a polar solvent, and water; In the aqueous base liquid, the mass content of polyfunctional amine is 0.5%~5%, the mass content of bimetallic coordinated COF nanoparticles is 0.1%~0.5%, the mass content of surfactant is 0.05%~2%, and the mass content of polar solvent is 3%~10%. The aqueous solution is obtained by adjusting the pH of the aqueous base liquid to 7-8; The pH adjuster used to adjust the pH value is an alkaline pH adjuster.
[0013] Preferably, the polyfunctional amine includes one or more of aromatic amines, aliphatic amines, and alicyclic amines; The surfactant includes sodium dodecyl sulfate or sodium lauryl sulfate; The polar solvents include dimethyl sulfoxide and / or N-methylpyrrolidone.
[0014] Preferably, the oil phase solution comprises pyromellitic trimethylol chloride, rigid tetramethylol chloride monomer, and oil phase solvent; The rigid tetraacryl chloride monomer includes at least one of 2,2',4,4'-biphenyltetracarboxylic chloride, pyromellitictetracarboxylic chloride and triptenetetracarboxylic chloride; The oil phase solvent includes n-hexane and cyclohexane in a volume ratio of 6~9:1~4; In the oil phase solution, the mass content of pyromellitic trimethylol chloride is 0.1%~0.3%, and the mass content of rigid tetramethylol chloride monomer is 0.03%~0.08%.
[0015] Preferably, the post-treatment solution comprises polyvinyl alcohol, glycerol, sodium dodecyl sulfate, and water; The post-treatment solution contains 1% to 4% polyvinyl alcohol, 0.5% to 2% glycerol, and 0.5% to 2% sodium dodecyl sulfate.
[0016] This invention also provides a method for preparing the reverse osmosis composite membrane described above, comprising the following steps: S1. The casting solution is coated onto one side of the nonwoven fabric layer and cured into a film by phase inversion to obtain a base film; the base film includes a nonwoven fabric layer and a support layer formed on the nonwoven fabric layer. S2. Coat the support layer with an aqueous solution, let it dry on the surface, then coat it with an oil solution. After heat curing, a polyamide separation layer is formed, and a nascent aromatic polyamide reverse osmosis membrane is obtained. S3. After rinsing the nascent aromatic polyamide reverse osmosis membrane, a post-treatment solution is coated on the polyamide separation layer. After drying, a protective layer is obtained, thereby obtaining a reverse osmosis composite membrane.
[0017] Preferably, the rinsing method includes: (1) Rinse with deionized water; (2) Rinse with citric acid aqueous solution; (3) Rinse with deionized water; (4) Rinse with isopropanol aqueous solution; (5) Rinse with deionized water; (6) Rinse with an aqueous glycerol solution; In step (1), the rinsing temperature is 15~30℃ and the time is 1~5 min; In step (2), the mass concentration of the citric acid aqueous solution is 1%~5%, the rinsing temperature is 40~80℃, and the time is 1~5min; In step (3), the rinsing temperature is 15~30℃ and the time is 1~5 min; In step (4), the mass concentration of the isopropanol aqueous solution is 1%~10%, the rinsing temperature is 40~80℃, and the time is 1~5 min; In step (5), the rinsing temperature is 15~30℃ and the time is 1~5 min; In step (6), the mass concentration of the glycerol aqueous solution is 2%~6%, the rinsing temperature is 15~30℃, and the time is 1~5min.
[0018] This invention integrates a COF rigid framework, metal coordination crosslinking, and rigid tetraacryl chloride micropores to construct a reverse osmosis composite membrane with both high-temperature resistance and solvent resistance. This achieves synergistic enhancement rather than simple additive properties. The "triple crosslinking-dual-channel" synergistic design achieves a 1+1>2 effect, enabling the membrane to maintain excellent performance while being solvent- and high-temperature resistant. The triple crosslinking-dual-channel design refers to: (1) Covalent crosslinking: Polyimide + hexamethylenediamine-based film is solvent resistant; (2) Hydrogen bond crosslinking: COF tertiary amine / imine nitrogen + polyamide carboxyl group is stable at high temperature; (3) Coordination crosslinking: Cu 2+ / Zn 2+ + COF nitrogen atom / polyamide carboxyl group dual resistance enhancement; (4) Channel 1: Free volume channel of polyamide network formed by crosslinking of m-phenylenediamine (MPD)-acyl chloride; (5) Channel 2: Sub-nano channels constructed from rigid tetraacyl chloride monomers. Detailed Implementation
[0019] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] The present invention provides a reverse osmosis composite membrane, comprising a non-woven fabric layer, a support layer, a polyamide separation layer and a protective layer sequentially laminated together; The polyamide separation layer is formed by interfacial polymerization of an aqueous solution and an oil solution on a support layer; the aqueous solution is obtained by adjusting the pH value of an aqueous base liquid comprising polyfunctional amines and bimetallic coordinated COF nanoparticles; the oil solution comprises pyromellitic trimethylol chloride and rigid tetramethylol chloride monomers. The protective layer is prepared on the polyamide separation layer by a post-treatment solution.
[0021] In some embodiments of the present invention, the thickness of the nonwoven layer is 90-100 μm, for example, 93 μm. The air permeability of the nonwoven layer is 1-20 cc / cm². 2 / s, for example, 5 cc / cm 2 / s.
[0022] In some embodiments of the present invention, the support layer is formed by curing a casting solution on the surface of a nonwoven fabric layer; the casting solution comprises polyimide, N-methylpyrrolidone, and hexamethylenediamine; the mass ratio is 10~20:80~90:0.75~3.75, for example 17:83:1.5, 12:88:2. The amino groups of hexamethylenediamine undergo an aminolysis reaction with the imide rings on the polyimide molecular chain, resulting in ring opening and the formation of intermolecular amide bond crosslinks, connecting the originally linear polyimide molecular chains into a three-dimensional network structure, thus giving the support layer solvent resistance.
[0023] The casting solution is prepared according to the following method: Polyimide was dissolved in N-methylpyrrolidone, and then hexamethylenediamine was added. The mixture was stirred and mixed at 40-70°C, and after degassing and cooling, a casting solution was obtained.
[0024] The mixing temperature is 55°C; the time is 12-24 hours, for example, 18 hours. Degassing and cooling are carried out in a degassing tank. The vacuum level of degassing and cooling is 2-4 inches of mercury, for example, 3 inches of mercury; the degassing time is 3-12 hours, for example, 8 hours.
[0025] In some embodiments of the present invention, the thickness of the support layer is 25~60 μm, for example 38 μm.
[0026] In this invention, the polyamide separation layer is formed by an interfacial polymerization reaction between an aqueous solution and an oil solution on a support layer. The thickness of the polyamide separation layer is 100~300 nm, for example, 200 nm.
[0027] In some embodiments of the present invention, the aqueous base liquid is composed of a polyfunctional amine, bimetallic coordinated COF nanoparticles, a surfactant, a polar solvent, and water.
[0028] In some embodiments of the present invention, the polyfunctional amine is one or more of aromatic amines, aliphatic amines, and alicyclic amines; specifically, it is one or more of m-phenylenediamine, ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, N(2-hydroxyethyl)ethylenediamine, 1,2-diaminocyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, diethylenetriamine, m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, mesitylenetriamine, piperazine, and 4-aminomethylpiperazine.
[0029] In some embodiments of the present invention, bimetallic coordinated COF nanoparticles are prepared using a solvothermal method. The preparation method of the bimetallic coordinated COF nanoparticles includes the following steps: A. Synthesis of COFTpDATB nanoparticles: 3,3′-diamine-Tellerg base (DATB) and 1,3,5-tricarboxymethyl phloroglucinol (Tp) were ultrasonically dispersed in a mixed solvent, then mixed with an aqueous acetic acid solution, degassed, and reacted at 110-130℃ to obtain COFTpDATB nanoparticles. B. An ethanol solution containing copper nitrate trihydrate and zinc nitrate hexahydrate was added dropwise to an ethanol dispersion containing COFTpDATB nanoparticles, and the reaction was carried out at 40~60℃ to obtain bimetallic coordinated COF nanoparticles (M-COFTpDATB).
[0030] Regarding step A: Synthesis of COFTpDATB nanoparticles: 3,3′-diamine-telegol base (DATB) and 1,3,5-tricarboxymethyl phloroglucinol (Tp) were ultrasonically dispersed in a mixed solvent, then mixed with an aqueous acetic acid solution, degassed, and reacted at 110-130℃ to obtain TpDATB covalent organic framework (COFTpDATB) nanoparticles.
[0031] In some embodiments of the present invention, the molar ratio of 3,3′-diamine-telegol (DATB) to 1,3,5-tricarboxymethylphloroglucinol (Tp) is 0.5~1.5:0.5~1.5, for example, 1:1.
[0032] In this invention, the mixed solvent is 1,4-dioxane, mesitylene, and n-butanol, with a volume ratio of 4~6:0.5~1.5:0.5~1.5, for example, 5:1:1. Compared with conventional synthesis methods, this invention introduces n-butanol as a co-solvent into the solvent system to regulate the nucleation rate of COF, resulting in a narrower particle size distribution of the obtained COFTpDATB nanoparticles. This invention does not impose any special limitations on the amount of the mixed solvent; it can be used for the ultrasonic dispersion of 3,3′-diamine-teleglerin (DATB) and 1,3,5-tricarboxymethyl phloroglucinol (Tp). In some embodiments of this invention, the ratio of the total amount of 3,3′-diamine-teleglerin (DATB) and 1,3,5-tricarboxymethyl phloroglucinol (Tp) to the amount of the mixed solvent is 0.2 mol: 2000 mL.
[0033] In some embodiments of the present invention, the ultrasonic dispersion time is 8 to 12 minutes, for example, 10 minutes.
[0034] In this invention, an aqueous acetic acid solution is used as a catalyst, with a mass concentration of 6% to 18%, for example, 9%. The volume ratio of the aqueous acetic acid solution to 3,3′-diamine-teleglerin (DATB) is 0.05 to 0.3:1, for example, 0.1 to 0.3:1, specifically 0.2:1.
[0035] The degassing method is as follows: after sealing, the product is frozen with liquid nitrogen, vacuumed, and thawed in a cycle.
[0036] In some embodiments of the present invention, the reaction temperature is 120°C. The reaction time is 70-74 hours, for example, 72 hours.
[0037] After the reaction is complete, the process includes: cooling and filtering, washing three times each with anhydrous tetrahydrofuran and acetone, and vacuum drying to obtain COFTpDATB nanoparticles. The vacuum drying temperature is 50~70℃, for example 60℃; the time is 22~26h, for example 24h.
[0038] In this invention, the COFTpDATB nanoparticles have a particle size of 80~150 nm.
[0039] Regarding step B: An ethanol solution containing copper nitrate trihydrate and zinc nitrate hexahydrate was added dropwise to an ethanol dispersion containing COFTpDATB nanoparticles, and the reaction was carried out at 40~60℃ to obtain bimetallic coordinated COF nanoparticles (M-COFTpDATB).
[0040] In some embodiments of the present invention, the mass ratio of copper nitrate trihydrate, zinc nitrate hexahydrate, and COFTpDATB nanoparticles is 0.8~1.5:1~1.875:4.4~8.25.
[0041] In some embodiments of the present invention, in the ethanol solution containing copper nitrate trihydrate and zinc nitrate hexahydrate, the ratio of the total mass of copper nitrate trihydrate and zinc nitrate hexahydrate to the amount of ethanol is 1.8~3.375 g: 500 mL, for example, 2.25 g: 500 mL. In the ethanol dispersion containing COFTpDATB nanoparticles, the ratio of COFTpDATB nanoparticles to ethanol is 4.4~8.25 g: 1600 mL, for example, 5.5 g: 1600 mL.
[0042] In some embodiments of the present invention, the reaction temperature is 50°C, and the reaction time is 14-18 hours, for example, 16 hours.
[0043] After the reaction is complete, the process further includes: centrifugation, washing three times with ethanol, and vacuum drying to obtain bimetallic coordinated COF nanoparticles, denoted as M-COFTpDATB. The vacuum drying temperature is 50~70℃, for example 60℃; the time is 12~24 h, for example 24 h.
[0044] In some embodiments of the present invention, the surfactant is sodium dodecyl sulfate or sodium lauryl sulfate.
[0045] In some embodiments of the present invention, the polar solvent is dimethyl sulfoxide and / or N-methylpyrrolidone.
[0046] In some embodiments of the present invention, the aqueous base liquid contains 0.5% to 5% by mass, for example 2.5%; bimetallic coordinated COF nanoparticles contain 0.1% to 0.5% by mass, for example 0.4% or 0.2%; surfactants contain 0.05% to 2% by mass, for example 0.1%; and polar solvents contain 3% to 10% by mass, for example 7%.
[0047] The present invention does not impose any special limitations on the preparation method of the aqueous base liquid. In some embodiments of the present invention, the preparation method of the aqueous base liquid includes the following steps: mixing polyfunctional amine, bimetallic coordinated COF nanoparticles, surfactant, polar solvent and water at room temperature to obtain an aqueous base liquid.
[0048] In some embodiments of the present invention, the aqueous solution is obtained by adjusting the pH of an aqueous base liquid to 7-8. The pH adjuster used for adjusting the pH is preferably an alkaline pH adjuster, more preferably NaOH.
[0049] In this invention, the pH value of the aqueous solution is limited to 7-8, which is conducive to the absorption of hydrochloric acid molecules, a byproduct of the interfacial polymerization process, and to the formation of highly cross-linked polyamides. If the pH is too low or too high, the amide bonds are prone to hydrolysis, which affects the separation performance of the polyamide separation layer.
[0050] In some embodiments of the present invention, the oil phase solution is composed of pyromellitic tricarboxylate chloride, a rigid tetraacryl chloride monomer, and an oil phase solvent. The rigid tetraacryl chloride monomer is at least one selected from 2,2',4,4'-biphenyltetracarboxylate chloride, pyromellitic tetracarboxylate chloride, and tripterene tetraacryl chloride. The oil phase solvent is n-hexane and cyclohexane in a volume ratio of 6-9:1-4, such as 9:1, 8:2, 7:3, or 6:4, preferably 7:3. In the oil phase solution, the mass content of pyromellitic tricarboxylate chloride is 0.1%-0.3%, such as 0.25%; the mass content of the rigid tetraacryl chloride monomer is 0.03%-0.08%, such as 0.05% or 0.03%.
[0051] This invention does not impose any particular limitations on the preparation method of the oil phase solution. In some embodiments of this invention, the preparation method of the oil phase solution includes the following steps: mixing trimesoyl chloride, rigid tetraacryl chloride monomer, and oil phase solvent at room temperature, then ultrasonically dispersing, allowing to stand, and confirming that there is no turbidity or precipitation to obtain the oil phase solution. The ultrasonic dispersion time is 10-15 min (e.g., 12 min) to ensure complete dissolution of the monomer. The standing time is 5-7 min, e.g., 5 min.
[0052] In this invention, the protective layer is used to protect the polyamide layer, while also enhancing surface hydrophilicity and improving anti-fouling ability.
[0053] In some embodiments of the present invention, the post-treatment solution is composed of polyvinyl alcohol, glycerol, sodium dodecyl sulfate, and water. The degree of alcoholysis of the polyvinyl alcohol is ≥99%. In the post-treatment solution, the mass content of polyvinyl alcohol is 1%~4%, the mass content of glycerol is 0.5%~2%, and the mass content of sodium dodecyl sulfate is 0.5%~2%.
[0054] The present invention does not impose any special restrictions on the preparation method of the post-treatment solution. The post-treatment solution can be obtained by mixing polyvinyl alcohol, glycerol, sodium dodecyl sulfate and water.
[0055] In some embodiments of the present invention, the thickness of the protective layer is 100~500 nm, for example 120 nm.
[0056] This invention also provides a method for preparing the reverse osmosis composite membrane described above, comprising the following steps: S1. The casting solution is coated onto one side of the nonwoven fabric layer and cured into a film by phase inversion to obtain a base film; the base film includes a nonwoven fabric layer and a support layer formed on the nonwoven fabric layer. S2. Coat the support layer with an aqueous solution, let it dry on the surface, then coat it with an oil solution. After heat curing, a polyamide separation layer is formed, and a nascent aromatic polyamide reverse osmosis membrane is obtained. S3. After rinsing the nascent aromatic polyamide reverse osmosis membrane, a post-treatment solution is coated on the polyamide separation layer. After drying, a protective layer is obtained, thereby obtaining a reverse osmosis composite membrane.
[0057] Regarding step S1: In some embodiments of the present invention, the coating method is slot extrusion. The coating amount of the casting solution on the nonwoven fabric layer is 25~35 g / m². 2 For example, 30 g / m 2 The phase transformation curing temperature is 15~20℃, for example, 18℃; the time is 30~120 s, for example, 60 s. The phase transformation curing is carried out in deionized water. After the phase transformation curing, the process further includes: rinsing with RO water at 25~35℃ (for example, 30℃), followed by annealing in RO water at 45~55℃ (for example, 50℃), and removing excess surface moisture with a water-absorbing plate to obtain the base film. The annealing time is 2~4 min, for example, 3 min.
[0058] Regarding step S2: The present invention does not impose any special restrictions on the amount of coating of the aqueous solution; generally, it allows for excessive coating.
[0059] The present invention does not impose any special limitations on the surface drying method; any surface drying method well known to those skilled in the art can be used.
[0060] In some embodiments of the present invention, the oil phase solution is coated by slot extrusion.
[0061] In some embodiments of the present invention, the temperature of the thermosetting treatment is 40~80°C, for example 60°C; and the time is 1~5 min, for example 3 min.
[0062] Regarding step S3: In some embodiments of the present invention, the rinsing method includes: (1) Rinse with deionized water; (2) Rinse with citric acid aqueous solution; (3) Rinse with deionized water; (4) Rinse with isopropanol aqueous solution; (5) Rinse with deionized water; (6) Rinse with glycerol aqueous solution.
[0063] In step (1), the rinsing temperature is 15~30℃, for example 20℃; the time is 1~5 min, for example 2 min.
[0064] In step (2), the mass concentration of the citric acid aqueous solution is 1%~5%, for example, 3%. The rinsing temperature is 40~80℃, for example, 60℃; the rinsing time is 1~5 min, for example, 5 min.
[0065] In step (3), the rinsing temperature is 15~30℃, for example 20℃; the time is 1~5 min, for example 2 min.
[0066] In step (4), the mass concentration of the isopropanol aqueous solution is 1%~10%, for example, 3%. The rinsing temperature is 40~80℃, for example, 60℃; the rinsing time is 1~5 min, for example, 5 min.
[0067] In step (5), the rinsing temperature is 15~30℃, for example 20℃; the time is 1~5 min, for example 2 min.
[0068] In step (6), the mass concentration of the glycerol aqueous solution is 2% to 6%, for example, 3%. The rinsing temperature is 15 to 30°C, for example, 25°C; and the time is 1 to 5 min, for example, 5 min.
[0069] In some embodiments of the present invention, the coating amount of the post-treatment solution on the polyamide separation layer is 100~140 mg / m². 2 For example, 120 mg / m 2 .
[0070] In some embodiments of the present invention, the drying temperature is 60~90°C, for example 80°C; and the drying time is 2~8 min, for example 2 min.
[0071] The present invention does not impose any special restrictions on the source of the raw materials used above, and they can be commercially available.
[0072] In this invention: 1. Bimetallic Coordination COF Design: Introducing Cu 2+ and Zn 2+ Bimetallic coordination center, Cu 2+ Provides stable anchoring, structural rigidity, and prevents COF skeleton collapse; Zn 2+This provides dynamic bonding, enabling thermal stress dissipation over a wide temperature range (25~90℃), preventing particle breakage and re-agglomeration caused by localized stress concentration. Furthermore, the COF preparation method in this invention introduces n-butanol as a co-solvent into the solvent system of conventional synthesis methods. n-Butanol adjusts the polarity of the mixed solvent, regulating the nucleation rate of COF, slowing down the monomer diffusion rate, and resulting in a narrower particle size distribution (80~150 nm). The hydroxyl groups of n-butanol may also form hydrogen bonds with residual polar groups on the COF surface, forming a solvation layer on the particle surface, which to some extent assists in subsequent redispersion. Simultaneously, Cu... 2+ / Zn 2+ The bimetallic coordination design further enhances the dispersion stability of the particles: Cu 2+ Provides strong coordination and anchoring, maintaining the structural integrity of the COF framework; Zn 2+ The dynamic coordination bonds can dissipate heat stress through reversible fracture-reorganization within a wide temperature range of 25~90℃, preventing particle aggregation caused by temperature changes and effectively reducing agglomeration.
[0073] 2. In this invention, the addition of rigid tetraacryl chloride monomer (preferably 2,2',4,4'-biphenyltetracarboxylic chloride) is mainly based on the following effects: a. Increased crosslinking density: Tetraacyl chloride monomer contains four acyl chloride functional groups. After reacting with polyfunctional amines (such as m-phenylenediamine), it can form a polyamide network structure with a higher crosslinking density than pyromellitic trimethylolpropionate chloride (trifunctional group), thereby improving the salt rejection rate and solvent resistance of the membrane.
[0074] b. Improved surface morphology: Literature studies have shown that the addition of tetraacyl chloride monomer can make the surface of polyamide layer smoother, reduce surface defects, and improve the long-term operational stability of the membrane.
[0075] c. Synergistic effect with COF: Bimetallic coordination COF mainly provides sub-nanometer-scale channels and dynamic coordination bonds, achieving improved flux and high-temperature stability; tetraacyl chloride monomer mainly provides a highly cross-linked network, achieving improved salt rejection and solvent resistance.
[0076] 3. Solvent system optimization in this invention: Rigid tetraacryl chloride monomers (tetrafunctional monomers) are prone to precipitation in nonpolar solvents (n-hexane) due to their strong polarity and high molecular rigidity. Precipitation can lead to uneven interfacial polymerization or the formation of defects. To address this, this invention has made the following optimizations to improve solubility while maintaining the stability of the water-oil interface during the interfacial polymerization reaction: ① Solvent optimization: A mixed solvent of n-hexane and cyclohexane was used. The polarity of cyclohexane is slightly higher than that of n-hexane (dielectric constant: cyclohexane 2.0 vs n-hexane 1.9), which can improve the solubility of tetraacryl chloride monomer while maintaining immiscibility with the aqueous phase.
[0077] ② Preferred monomers: 2,2',4,4'-biphenyltetracarboxylic chloride is preferred as a rigid tetracarboxylic chloride monomer, as its solubility in alkane solvents is better than that of pyromellitic tetracarboxylic chloride.
[0078] ③ Concentration control: The concentration should be controlled within the range of 0.03wt% to 0.08wt% to avoid monomer precipitation due to excessive concentration.
[0079] ④ Preparation process: After the organic phase solution is prepared, it is ultrasonically dispersed for 10-15 min to ensure that the monomer is completely dissolved, and then allowed to stand for 5-7 min to confirm that there is no turbidity or precipitation before it is used for interfacial polymerization reaction.
[0080] To further illustrate the present invention, the following detailed description of a reverse osmosis composite membrane and its preparation method provided by the present invention is provided in conjunction with embodiments, but it should not be construed as limiting the scope of protection of the present invention.
[0081] Example 1
[0082] 1. Preparation of casting solution: Dissolve 17 parts by weight of polyimide in 83 parts by weight of N-methylpyrrolidone, and then add 1.5 parts by weight of hexamethylenediamine; stir and mix at 55°C for 18 h, and then transfer to a degassing tank for degassing and cooling (the vacuum degree of degassing and cooling is 3 inches of mercury, and the degassing time is 8 h) to obtain a uniform and transparent casting solution.
[0083] 2. Preparation of the base film: The casting solution was coated onto a nonwoven fabric (93 μm thick, 5 cc / cm² air permeability) using a slit extrusion method. 2 The coating amount is 30 g / m² on one side of the surface (s / s). 2 The film is solidified by immersion in 18℃ deionized water for 60 s for phase transformation, rinsed with 30℃ RO water, and then annealed in 50℃ RO water for 3 min. The water-absorbing plate removes excess water from the surface to form a support layer (thickness 38 μm), thus obtaining the base film.
[0084] 3. Preparation of bimetallic coordinated COF nanoparticles using a solvothermal method: 3-1. Synthesis of COFTpDATB nanoparticles: 0.1 mol of 3,3′-diamine-telegol (DATB) and 0.1 mol of 1,3,5-tricarboxymethyl phloroglucinol (Tp) were added to a pressure-resistant reaction tube containing 2000 mL of a mixed solvent (1,4-dioxane, mesitylene, and n-butanol in a volume ratio of 5:1:1) and ultrasonically dispersed for 10 min. A 9% (w / w) aqueous acetic acid solution was added as a catalyst (the volume ratio of the aqueous acetic acid solution to the 3,3′-diamine-telegol was 0.2:1). After sealing, the mixture was degassed three times by liquid nitrogen freezing, vacuuming, and thawing cycles. The reaction was carried out at 120 °C for 72 h. After cooling, the mixture was filtered and washed three times each with anhydrous tetrahydrofuran and acetone. The mixture was then vacuum dried at 60 °C for 24 h to obtain COFTpDATB nanoparticles with a particle size of 80–150 nm.
[0085] 3-2. Preparation of bimetallic coordinated COF nanoparticles: First, 5.5g of COFTpDATB nanoparticles were dispersed in 1600 mL of ethanol to obtain an ethanol dispersion containing COFTpDATB nanoparticles. Dissolve 1g of copper nitrate trihydrate and 1.25g of zinc nitrate hexahydrate in 500 mL of ethanol to obtain an ethanol solution containing copper nitrate trihydrate and zinc nitrate hexahydrate. An ethanol solution containing copper nitrate trihydrate and zinc nitrate hexahydrate was added dropwise to an ethanol dispersion containing COFTpDATB nanoparticles. The reaction was carried out at 50°C for 16 h. After the reaction was completed, the nanoparticles were centrifuged, washed three times with ethanol, and dried under vacuum at 60°C for 24 h to obtain bimetallic coordinated COF nanoparticles, denoted as M-COFTpDATB.
[0086] 3-3. Preparation of aqueous solution: A polyfunctional amine (m-phenylenediamine), bimetallic coordinated COF nanoparticles (M-COFTpDATB), a surfactant (sodium dodecyl sulfate), a polar solvent (dimethyl sulfoxide), and deionized water were mixed at room temperature to obtain an aqueous base solution. The aqueous base solution contained 2.5% polyfunctional amine, 0.4% bimetallic coordinated COF nanoparticles, 0.1% surfactant, and 7% polar solvent. The pH of the aqueous base solution was adjusted to 7.8 using sodium hydroxide to obtain an aqueous solution.
[0087] 3-4. Preparation of oil phase solution: An acyl halide (pyromellitic tricarboxylate chloride), a rigid tetraacyl chloride monomer (2,2',4,4'-biphenyltetracarboxylate chloride), and an oil phase solvent (n-hexane and cyclohexane, volume ratio 7:3) were mixed at room temperature and ultrasonically dispersed for 12 min to ensure complete dissolution of the monomer. After standing for 5 min to confirm the absence of turbidity or precipitation, an oil phase solution was obtained. The oil phase solution contained 0.25% acyl halide and 0.05% rigid tetraacyl chloride monomer by mass.
[0088] 3-5. Coat the support layer of the base membrane with an aqueous solution. After surface drying, coat the oil solution by slit extrusion. After heat curing at 60℃ for 3 min, a polyamide separation layer (200 nm thick) is formed, and a nascent aromatic polyamide reverse osmosis membrane is obtained. 3-6. Rinse the nascent aromatic polyamide reverse osmosis membrane: First, rinse with 20°C deionized water for 2 min, then rinse with 60°C citric acid aqueous solution (3% by mass) for 5 min, then rinse with 20°C deionized water for 2 min, then rinse with 60°C isopropanol aqueous solution (3% by mass) for 5 min, then rinse with 20°C deionized water for 2 min, and finally rinse with 25°C glycerol aqueous solution (3% by mass) for 5 min.
[0089] 3-7. Preparation of post-treatment solution: Polyvinyl alcohol, glycerol, sodium dodecyl sulfate and water are mixed to obtain a post-treatment solution; in the post-treatment solution, the mass content of polyvinyl alcohol is 1.5%, the mass content of glycerol is 1%, and the mass content of sodium dodecyl sulfate is 1.2%.
[0090] The post-treatment solution (coating amount of 120 mg / m²) is applied to the polyamide separation layer after rinsing in steps 3-6. 2 After drying at 80℃ for 2 min, a protective layer (120 nm thick) is obtained, thus obtaining a reverse osmosis composite membrane.
[0091] Example 2
[0092] The difference from Example 1 is that the component content in the casting solution is different; That is: 1. Preparation of casting solution: Dissolve 12 parts by weight of polyimide in 88 parts by weight of N-methylpyrrolidone, and then add 2 parts by weight of hexamethylenediamine; stir and mix at 55°C for 18 h, and then transfer to a degassing tank for degassing and cooling (the vacuum degree of degassing and cooling is 3 inches of mercury, and the degassing time is 8 h) to obtain a uniform and transparent casting solution.
[0093] The remaining steps are the same as in Example 1, and a reverse osmosis composite membrane is obtained.
[0094] Example 3
[0095] The difference from Example 1 is that the mass content of the bimetallic coordinated COF nanoparticles is different. That is: 3-3, Preparation of aqueous solution: A polyfunctional amine (m-phenylenediamine), bimetallic coordinated COF nanoparticles (M-COFTpDATB), a surfactant (sodium dodecyl sulfate), a polar solvent (dimethyl sulfoxide), and deionized water were mixed at room temperature to obtain an aqueous base solution. The aqueous base solution contained 2.5% polyfunctional amine, 0.2% bimetallic coordinated COF nanoparticles, 0.1% surfactant, and 7% polar solvent. The pH of the aqueous base solution was adjusted to 7.8 using sodium hydroxide to obtain an aqueous solution.
[0096] The remaining steps are the same as in Example 1, and a reverse osmosis composite membrane is obtained.
[0097] Example 4
[0098] The difference from Example 1 is that the mass content of the rigid tetraacryl chloride monomer is different; That is: 3-4, Preparation of oil phase solution: An acyl halide (pyromellitic tricarboxylate chloride), a rigid tetraacyl chloride monomer (2,2',4,4'-biphenyltetracarboxylate chloride), and an oil phase solvent (n-hexane and cyclohexane, volume ratio 7:3) were mixed at room temperature and ultrasonically dispersed for 12 min to ensure complete dissolution of the monomer. After standing for 5 min to confirm the absence of turbidity or precipitation, an oil phase solution was obtained. The oil phase solution contained 0.25% acyl halide and 0.03% rigid tetraacyl chloride monomer by mass.
[0099] The remaining steps are the same as in Example 1, and a reverse osmosis composite membrane is obtained.
[0100] Comparative Example 1
[0101] The difference from Example 1 is that hexamethylenediamine is not added to the casting solution; That is: 1. Preparation of casting solution: 17 parts by weight of polyimide were dissolved in 83 parts by weight of N-methylpyrrolidone and stirred at 55°C for 18 h. After stirring, the mixture was transferred to a degassing tank for degassing and cooling (the vacuum degree of degassing and cooling was 3 inches of mercury, and the degassing time was 8 h) to obtain a uniform and transparent casting solution.
[0102] The remaining steps are the same as in Example 1, and a reverse osmosis composite membrane is obtained.
[0103] Comparative Example 2
[0104] The difference from Example 1 is that the aqueous solution does not contain bimetallic coordinated COF nanoparticles (M-COFTpDATB). That is: 3-3, Preparation of aqueous solution: A polyfunctional amine (m-phenylenediamine), a surfactant (sodium dodecyl sulfate), a polar solvent (dimethyl sulfoxide), and deionized water were mixed at room temperature to obtain an aqueous base solution. The aqueous base solution contained 2.5% polyfunctional amine, 0.1% surfactant, and 7% polar solvent by mass. The pH of the aqueous base solution was adjusted to 7.8 using sodium hydroxide to obtain an aqueous solution.
[0105] The remaining steps are the same as in Example 1, and a reverse osmosis composite membrane is obtained.
[0106] Comparative Example 3
[0107] The difference from Example 1 is that the oil phase solution does not contain rigid tetraacryl chloride monomer; That is: 3-4, Preparation of oil phase solution: The acyl halide (pyromellitic trimethylolpropionate chloride) and the oil phase solvent (n-hexane and cyclohexane, volume ratio 7:3) were mixed at room temperature and ultrasonically dispersed for 12 min to ensure complete dissolution of the monomer. After standing for 5 min to confirm the absence of turbidity or precipitation, the oil phase solution was obtained. The mass content of the acyl halide in the oil phase solution was 0.25%.
[0108] The remaining steps are the same as in Example 1, and a reverse osmosis composite membrane is obtained.
[0109] Comparative Example 4
[0110] The difference from Example 1 is that the oil phase solvent does not contain cyclohexane; That is: 3-4, Preparation of oil phase solution: An acyl halide (pyromellitic tricarboxylate chloride), a rigid tetraacyl chloride monomer (2,2',4,4'-biphenyltetracarboxylate chloride), and an oil phase solvent (n-hexane) were mixed at room temperature and ultrasonically dispersed for 12 min to ensure complete dissolution of the monomer. After standing for 5 min to confirm the absence of turbidity or precipitation, an oil phase solution was obtained. The oil phase solution contained 0.25% by mass of the acyl halide and 0.05% by mass of the rigid tetraacyl chloride monomer.
[0111] The remaining steps are the same as in Example 1, and a reverse osmosis composite membrane is obtained.
[0112] Comparative Example 5
[0113] The difference from Example 1 is that the mixed solvent in the synthesis of COFTpDATB nanoparticles does not contain n-butanol; That is: 3-1, Synthesis of COFTpDATB nanoparticles: 0.1 mol of 3,3′-diamine-telegol (DATB) and 0.1 mol of 1,3,5-tricarboxymethyl phloroglucinol (Tp) were added to a pressure-resistant reaction tube containing 2000 mL of a mixed solvent (1,4-dioxane and mesitylene, volume ratio 5:1) and ultrasonically dispersed for 10 min. A 9% (w / w) aqueous acetic acid solution was added as a catalyst (the volume ratio of the aqueous acetic acid solution to 3,3′-diamine-telegol was 0.2:1). After sealing, the mixture was degassed three times by liquid nitrogen freezing, vacuuming, and thawing cycles. The reaction was carried out at 120 °C for 72 h, cooled, filtered, and washed three times each with anhydrous tetrahydrofuran and acetone. The mixture was then vacuum dried at 60 °C for 24 h to obtain COFTpDATB nanoparticles with a particle size of 80–150 nm.
[0114] The remaining steps are the same as in Example 1, and a reverse osmosis composite membrane is obtained.
[0115] Performance testing: The reverse osmosis composite membranes prepared in the above examples and comparative examples were tested under the following four conditions: Condition 1: The membrane is installed in the membrane tank and rinsed in pure water for 15 minutes at a pressure of 1.03 MPa, a temperature of 25°C, and an influent flow rate of 1.1 GPM. Then, it is circulated in a 1500 ppm sodium chloride aqueous solution at a pressure of 1.03 MPa, a temperature of 25°C, and an influent flow rate of 1.1 GPM for 15 minutes. The volume of the permeate and the concentration of sodium chloride in it are measured.
[0116] Condition 2: Compared to Condition 1, the rinsing and testing temperature is 80℃.
[0117] Condition 3: Compared to Condition 1, the rinsing is changed to rinsing with a 15 wt% DMF solution for 1 hour.
[0118] Condition 4: Compared to Condition 1, the rinsing and testing temperature is 80℃, and the rinsing is changed to rinsing with 15 wt% DMF solution for 1 hour.
[0119] The water permeation rate of the reverse osmosis composite membrane is calculated according to formula (1): Equation (1); In equation (1), J Let gfd be the water flux. Q Water permeability, in L; A The effective membrane area of the composite reverse osmosis membrane is m. 2 ; t For time, h; The desalination rate of the reverse osmosis composite membrane is calculated according to formula (2): Equation (2); In equation (2), R The desalination rate is %; C f The concentration of sodium chloride in the original solution, in ppm. C p The concentration of sodium chloride in the permeate is expressed in ppm.
[0120] The test results are shown in Table 1.
[0121] Table 1 Performance test results of the reverse osmosis composite membranes in the examples and comparative examples
[0122]
[0123] As can be seen from Table 1, the reverse osmosis composite membrane provided by this invention possesses high-temperature stability and solvent resistance. Furthermore, the process of this invention is consistent with existing conventional reverse osmosis membrane production lines, requiring minimal equipment modifications, which is beneficial for industrial production.
[0124] The descriptions of the above embodiments are merely illustrative of the methods and core ideas of the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A reverse osmosis composite membrane, characterized in that, It includes a nonwoven fabric layer, a support layer, a polyamide separation layer, and a protective layer that are sequentially laminated; The polyamide separation layer is formed by interfacial polymerization of an aqueous solution and an oil solution on a support layer; the aqueous solution is obtained by adjusting the pH value of an aqueous base liquid comprising polyfunctional amines and bimetallic coordinated COF nanoparticles; the oil solution comprises pyromellitic trimethylol chloride and rigid tetramethylol chloride monomers. The protective layer is prepared on the polyamide separation layer by a post-treatment solution.
2. The reverse osmosis composite membrane according to claim 1, characterized in that, The support layer is formed by curing a casting solution on the surface of a nonwoven fabric layer. The casting solution comprises polyimide, N-methylpyrrolidone, and hexamethylenediamine in a mass ratio of 10-20:80-90:0.75-3.
75.
3. The reverse osmosis composite membrane according to claim 1, characterized in that, The preparation method of the bimetallic coordinated COF nanoparticles includes the following steps: A. 3,3′-diamine-telegol base and 1,3,5-tricarboxymethyl phloroglucinol were ultrasonically dispersed in a mixed solvent, mixed with an aqueous acetic acid solution, degassed, and reacted at 110~130℃ to obtain COFTpDATB nanoparticles. B. An ethanol solution containing copper nitrate trihydrate and zinc nitrate hexahydrate was added dropwise to an ethanol dispersion containing COFTpDATB nanoparticles, and the reaction was carried out at 40~60℃ to obtain bimetallic coordinated COF nanoparticles.
4. The reverse osmosis composite membrane according to claim 3, characterized in that, The mixed solvent comprises 1,4-dioxane, mesitylene, and n-butanol in a volume ratio of 4~6:0.5~1.5:0.5~1.5; The molar ratio of the 3,3′-diamine-telegol base to the 1,3,5-tricarboxymethylphloroglucinol is 0.5~1.5:0.5~1.5; The COFTpDATB nanoparticles have a particle size of 80~150 nm; The mass ratio of copper nitrate trihydrate, zinc nitrate hexahydrate, and COFTpDATB nanoparticles is 0.8~1.5:1~1.875:4.4~8.
25.
5. The reverse osmosis composite membrane according to claim 1, characterized in that, The aqueous base liquid comprises a polyfunctional amine, bimetallic coordinated COF nanoparticles, a surfactant, a polar solvent, and water; In the aqueous base liquid, the mass content of polyfunctional amine is 0.5%~5%, the mass content of bimetallic coordinated COF nanoparticles is 0.1%~0.5%, the mass content of surfactant is 0.05%~2%, and the mass content of polar solvent is 3%~10%. The aqueous solution is obtained by adjusting the pH of the aqueous base liquid to 7-8; The pH adjuster used to adjust the pH value is an alkaline pH adjuster.
6. The reverse osmosis composite membrane according to claim 5, characterized in that, The polyfunctional amines include one or more of aromatic amines, aliphatic amines, and alicyclic amines; The surfactant includes sodium dodecyl sulfate or sodium lauryl sulfate; The polar solvents include dimethyl sulfoxide and / or N-methylpyrrolidone.
7. The reverse osmosis composite membrane according to claim 1, characterized in that, The oil phase solution comprises pyromellitic trimethylol chloride, rigid tetramethylol chloride monomer and oil phase solvent; The rigid tetraacryl chloride monomer includes at least one of 2,2',4,4'-biphenyltetracarboxylic chloride, pyromellitictetracarboxylic chloride and triptenetetracarboxylic chloride; The oil phase solvent includes n-hexane and cyclohexane in a volume ratio of 6~9:1~4; In the oil phase solution, the mass content of pyromellitic trimethylol chloride is 0.1%~0.3%, and the mass content of rigid tetramethylol chloride monomer is 0.03%~0.08%.
8. The reverse osmosis composite membrane according to claim 1, characterized in that, The post-treatment solution comprises polyvinyl alcohol, glycerol, sodium dodecyl sulfate, and water; The post-treatment solution contains 1% to 4% polyvinyl alcohol, 0.5% to 2% glycerol, and 0.5% to 2% sodium dodecyl sulfate.
9. A method for preparing the reverse osmosis composite membrane according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1. The casting solution is coated onto one side of the nonwoven fabric layer and cured into a film by phase inversion to obtain a base film; the base film includes a nonwoven fabric layer and a support layer formed on the nonwoven fabric layer. S2. Coat the support layer with an aqueous solution, let it dry on the surface, then coat it with an oil solution. After heat curing, a polyamide separation layer is formed, and a nascent aromatic polyamide reverse osmosis membrane is obtained. S3. After rinsing the nascent aromatic polyamide reverse osmosis membrane, a post-treatment solution is coated on the polyamide separation layer. After drying, a protective layer is obtained, thereby obtaining a reverse osmosis composite membrane.
10. The preparation method according to claim 9, characterized in that, The rinsing method includes: (1) Rinse with deionized water; (2) Rinse with citric acid aqueous solution; (3) Rinse with deionized water; (4) Rinse with isopropanol aqueous solution; (5) Rinse with deionized water; (6) Rinse with an aqueous glycerol solution; In step (1), the rinsing temperature is 15~30℃ and the time is 1~5 min; In step (2), the mass concentration of the citric acid aqueous solution is 1%~5%, the rinsing temperature is 40~80℃, and the time is 1~5min; In step (3), the rinsing temperature is 15~30℃ and the time is 1~5 min; In step (4), the mass concentration of the isopropanol aqueous solution is 1%~10%, the rinsing temperature is 40~80℃, and the time is 1~5min; In step (5), the rinsing temperature is 15~30℃ and the time is 1~5 min; In step (6), the mass concentration of the glycerol aqueous solution is 2%~6%, the rinsing temperature is 15~30℃, and the time is 1~5 min.